Perceived Risk and Its Components: A Model and Empirical Test - Bettman, James R. (Journal of Marketing Research, 1973)
A theoretical model and measurement system for perceived risk and its components is developed and empirically tested for nine product types. Regression analysis is used to consider both additive and multiplicative relationships. The results generally support the hypothesized model.